ANALISIS SWOT TERHADAP UPAYA MEMBENTUK SANTRI MENJADI TANGGUH DAN MANDIRI (STUDI PESANTREN MUHAMMADIYAH DARUL ARQOM DEPOK) - Mahmudin Sudin; Gilang Haryadi (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2023)
The purpose of this study was to find out (1) the dynamics of education at the Muhammadiyah Darul Arqom Depok Modern Islamic Boarding School in shaping the souls of students to become strong and independent scholars. (2) Efforts by the leadership of the Modern Muhammadiyah Islamic Boarding School Darul Arqom Depok to shape the souls of the students to become strong and independent clerics. (3) Inhibiting and supporting factors in the efforts of modernIslamic boarding schools to shape the souls of students to become strong and independent scholars. The approach in this study uses a qualitative approach. The data analysis used in this study is SWOT analysis, which uses the SWOT analysis model to compare external factors, opportunities and threats with internal factors of strengths and weaknesses.The results of the study show that: (1) The dynamics of education at the Modern Muhammadiyah Islamic Boarding School Darul Arqom Depok in shaping the souls of students to become tough and independent scholars is the establishment of the Muhammadiyah Darul Arqom Islamic Boarding School as a forum for cadre of scholars who are the hope of society(2) The Efforts of the Leaders of the Muhammadiyah Darul Arqom Modern Islamic Boarding School Depok forms the souls of students to become tough and independent scholars by providing specialization programs, tahfizul Al-Qur'an, bilingual Arabic and English as well as training students to get used toengaging in social activities with the community. (3) Inhibiting and supporting factors in the efforts of modern Islamic boarding schools to shape the souls of students to become strong and independent scholars. The inhibiting factor is a sense of responsibility as an educator who has not been maximizedin teaching, facilities and infrastructure that have not been adequate to support the learning process. The supporting factors are the collaboration of the development team and supervision from the Board of Trustees of the Islamic Boarding School